ChemInform Abstract: Crystallographic and Magnetic Descriptions of a Novel Erbium Rich Aluminide: Er10Co1+xAl3‐x (x = 0.30). Issue 47 (November 2015) - Nasri, N.; Pasturel, Mathieu; Dorcet, V.; Belgacem, B.; Ben Hassen, R.; Tougait, O.
Abstract: Er10 Co1.3 Al2.7 is prepared by arc melting of the elements followed by annealing (alumina crucible in evacuated silica ampoule, 1123 K, 1 week).